3-6x-6x=11+4-7x+x

Simple and best practice solution for 3-6x-6x=11+4-7x+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-6x-6x=11+4-7x+x equation:


Simplifying
3 + -6x + -6x = 11 + 4 + -7x + x

Combine like terms: -6x + -6x = -12x
3 + -12x = 11 + 4 + -7x + x

Combine like terms: 11 + 4 = 15
3 + -12x = 15 + -7x + x

Combine like terms: -7x + x = -6x
3 + -12x = 15 + -6x

Solving
3 + -12x = 15 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
3 + -12x + 6x = 15 + -6x + 6x

Combine like terms: -12x + 6x = -6x
3 + -6x = 15 + -6x + 6x

Combine like terms: -6x + 6x = 0
3 + -6x = 15 + 0
3 + -6x = 15

Add '-3' to each side of the equation.
3 + -3 + -6x = 15 + -3

Combine like terms: 3 + -3 = 0
0 + -6x = 15 + -3
-6x = 15 + -3

Combine like terms: 15 + -3 = 12
-6x = 12

Divide each side by '-6'.
x = -2

Simplifying
x = -2

See similar equations:

| 16+40+6-2= | | 6m+9m+5m=-1 | | 8x-6(-1)=-18 | | 12x-8y=-8 | | 5/13=19/x | | a(x)=2x+40(2x+60) | | 20y=5x | | 2x+11=8x-2 | | 6(2g+1)= | | 6x-55+x^2=0 | | 6-4-18+3+12= | | -4+5(x+1)=2x+3(x+3) | | b=75+18w | | x^3+8x^2+8x+64= | | G+12=2 | | X/7-x/8=2 | | cosb=0.1 | | 132=24c+28c | | 14/1-26/5 | | 20n=2150 | | -35=7(k-8) | | 2(-x-1)-3(5-3x)=4 | | 5x+x=9+4c-1+6 | | 10b+45= | | 4/5g=-7 | | x^3-3x^2-4x-12= | | 6x^2+9y^2-24x+18y-21=0 | | 4(3d+6)= | | 11+y=9y | | b=55+(15+8)w | | 25y=2544 | | 2f(8f+8)= |

Equations solver categories